Rebecca Wynn and Jack Kellythorne using a H-P 9000 Model 320 - Public Information Office, California Polytechnic State University::::::::: (1987)
Caption on back reads: 'Donations of equipment and money were fueling the momentum of the School of Engineering's Benchmark Campaign in 1987. Many corporations had contributed generously, such as Hewlett-Packard with its gifts last year totaling $1.2 million. Included in this was equipment valued at $680,000 for a computer-aided-design lab. Here seniors Rebecca Wynn and Jack Kellythorne work on a project using one of the H-P 9000 Model 320 computers.' Kellythorne is using a stylus and writing pad to draw the design that is displayed on the screen.